HUBUNGAN PENGETAHUAN DENGAN PERSEPSI MAHASISWI DALAM PENERIMAAN VAKSINASI HPV SEBAGAI UPAYA PENCEGAHAN KANKER SERVIKS - Dewi Ekowati; Ari Udiyono; Martini Martini; Mateus Sakundarno Adi (Jurnal Kesehatan Masyarakat (Undip), 2017)
Cervical cancer is an excessive and uncontrolled cell growth around the cervix. The main cause is HPV (Human Papilloma Virus). Primary prevention can be done with HPV vaccination. In Indonesia, many women who do not understand about HPV vaccination. The purpose of this research isto analyze the relationship of knowledge and perception with the acceptance of HPV vaccination among college women at the Faculty of Psychology Diponegoro University.This was an observational analytic study with cross-sectional approach. A proportional random sampling of 594 young women was recruited from colleges. A questionnaire was performed to assess demographics; HPV and cervical cancer-related health characteristics; and knowledge and beliefs toward HPV and cervical cancer. Correlation analysis is used to determine the relationship of knowledge and perception with acceptance of HPV vaccination. The results show that respondents have less of knowledge about cervical cancer and HPV vaccination (49%); most respondents were willing to receive HPV vaccination (70%). Statistical analysis showed thatknowledge was significantly associated with perceived seriousness of cervical cancer (p=0,024) and perceived barriers of vaccination (p=0,003). HPV vaccine has great potential to prevent cervical cancer.Understanding variables associated with acceptance of HPV vaccination may guide immunization initiativesand so increase the uptake rate among college women.